THE USE OF DIGITAL TECHNOLOGIES TO ENHANCE CREATIVE SKILLS IN VISUAL ARTS EDUCATION - Ataullayeva E’zoza Mansur qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article examines the role of digital technologies in developing students’ creative skills in visual arts lessons. Drawing on Shovdirov S.A.’s research, it highlights how digital tools, multimedia resources, and interactive platforms can support artistic literacy, independent thinking, and aesthetic development. The study also discusses pedagogical strategies for integrating technology into visual arts education to increase engagement, motivation, and the effectiveness of lessons.